The importance of including the C-terminal domain of PTP1B1-400 to identify potential antidiabetic inhibitors - Andrea Coronell-Tovar; Francisco Cortés-Benítez; Martin González-Andrade (Journal of Enzyme Inhibition and Medicinal Chemistry, 2023)
In the present work, we studied the inhibitory and kinetic implications of classical PTP1B inhibitors (chlorogenic acid, ursolic acid, suramin) using three enzyme constructs (hPTP1B1-285, hPTP1B1-321, and hPTP1B1-400). The results indicate that the unstructured region of PTP1B (300-400 amino acids) is very important both to obtain optimal inhibitory results and propose classical inhibition mechanisms (competitive or non-competitive) through kinetic studies. The IC50 calculated for ursolic acid and suramin using hPTP1B1-400 are around four and three times lower to the short form of the enzyme, the complete form of PTP1B, the one found in the cytosol (in vivo). On the other hand, we highlight the studies of enzymatic kinetics using the hPTP1B1-400 to know the type of enzymatic inhibition and to be able to direct docking studies, where the unstructured region of the enzyme can be one more option for binding compounds with inhibitory activity.